Bronchial carcinoma in patients with pre-existing unilateral lung disease. Issue 6 (December 1976) - Yoneyama, T; Naruke, T; Suemasu, K; Ishikawa, S
Abstract : Forty-six cases of primary bronchogenic carcinoma occurring in patients with other unilateral pleuropulmonary diseases were studied. In 37 cases (80-4%) carcinoma developed in the previously healthy lung. All but one squamous-cell carcinoma and all of five undifferentiated small-cell carcinomas developed in the previously healthy lung while 7 of 15 adenocarcinomas were in the lung with impaired ventilation. It is suggested that the bronchial epithelium of the healthy lung is more exposed to exogenous carcinogens than that of the diseased, underventilated lung, resulting in a higher risk of development of squamous-cell and undifferentiated small-cell carcinoma.